Adsorption of Para Nitro-phenol by activated carbon produced from Alhagi - Abd-Hadi, Ghufran Muafaq; Salman, Sami D. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This manuscript has present an experimental study for Para Nitro-phenol (PNP) removal from aqueous solution using by physiochemical Alhagi activated carbon (AAC). AAC was characterized using SEM to investigate surface morphology and BET to estimate the specific surface area. The best surface area of AAC was found to be 641.6 m2/gm which was obtained at 600ºC activation temperature and impregnation ratio of 1:1 of KOH. The investigated factors for PNP ions adsorption and their ranges such as initial concentration (10-50 mg/L), adsorption time (30-210 min), temperature (20-50ºC) and solution pH (4-10). Isotherm of adsorption and its kinetics were studied. The adsorption process was modeled statistically by an empirical model. The equilibrium data were fitted to the Langmuir and Freundlich isotherm models and the data found to be well represented by Langmuir isotherm. Pseudo- first order and pseudo- second order kinetic equations were utilized to study adsorption kinetics. It is found that the PNP adsorption on AAC fitted pseudo- second more adequately and the best removal efficiency was found to be 97.59%.